2014
DOI: 10.33818/ier.278035
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Exchange Rate Volatility by Macroeconomic Fundamentals in Pakistan

Abstract: What drives volatility in foreign exchange market in Pakistan? This paper undertakes an analysis of modelling exchange rate volatility in Pakistan by potential macroeconomic fundamentals well-known in the economic literature. For this monthly data on Pak Rupee exchange rates in the terms of major currencies (US Dollar, British Pound, Canadian Dollar and Japanese Yen) and macroeconomics fundamentals is taken from April, 1982 to November, 2011. The results show that the PKR-USD exchange rate volatility is influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…For example, Monica and Santhiyavali (2017) and Bouraoui and Phisuthtiwatcharavong (2015) confirmed that foreign exchange reserves significantly affect ERV. This result is in line with the findings of Jabeen and Khan (2014) and Khan (2013) that showed a long-run relationship between FXRES and ERV. However, Bayat et al (2014) examined the asymmetric nexus between the said variables and found that foreign reserves do not affect nominal exchange rates.…”
Section: Literature Reviewsupporting
confidence: 92%
See 1 more Smart Citation
“…For example, Monica and Santhiyavali (2017) and Bouraoui and Phisuthtiwatcharavong (2015) confirmed that foreign exchange reserves significantly affect ERV. This result is in line with the findings of Jabeen and Khan (2014) and Khan (2013) that showed a long-run relationship between FXRES and ERV. However, Bayat et al (2014) examined the asymmetric nexus between the said variables and found that foreign reserves do not affect nominal exchange rates.…”
Section: Literature Reviewsupporting
confidence: 92%
“…Chipili (2012) applied the same model and found a negative relationship between ERV and trade openness, suggesting more diversification in trade openness reduces fluctuations in exchange rates. However, Jabeen and Khan (2014) found a negative relationship between output volatility and ERV.…”
Section: Literature Reviewmentioning
confidence: 90%
“…MPOFU other two are insignificant. Jabeen and Khan (2014) also find insignificant results using monthly data and GARCH methods. However, these studies provide results based on high-frequency data, which differ with the theoretical model of Hau (2002), which states that the inverse relationship between real exchange rate volatility and trade openness occurs when using low-frequency data set.…”
mentioning
confidence: 95%
“…In the recent past, researchers indeed have focused on macroeconomic volatility (see, for instance, Ramey and Ramey, 2005). Yet only a few empirical studies analyzed the interlinkages between various macro-level volatilities (Morana, 2009;Jabeen and Khan, 2014). The empirical literature on the interlinkages between VRER, VCPI, VLMI, and VINT remained silent.…”
Section: Introductionmentioning
confidence: 99%
“…Kholdy and Sohrabian (1990) reported the causal relationship running from wholesale prices to ER. Jabeen and Khan (2014) documented that VRER is influenced by several macroeconomic volatilities. Similarly, Morana (2009) argued that there is a linkage between ER and macroeconomic volatility, namely VLMI and VCPI.…”
Section: Introductionmentioning
confidence: 99%